Assessments of Harvesting Regimes in Central Hardwood Forests under Climate and Fire Uncertainty. Issue 1 (7th September 2017) - Ma, Wu; Zhou, Mo
Abstract: In the absence of harvests and disturbances other than fire, central hardwood forests are predicted to undergo a species shift and decline in stocks because of climate change and increased fire frequencies. Here we quantified how various harvesting intensities and regimes would influence these forests in terms of the net present value (NPV) of harvests, tree species and size diversity, and carbon stock from 2010 to 2100. Partial, diameter-limit, and diameter-cap harvesting practices were assessed with cutting cycles of 10 and 20 years, respectively. We found that low intensity would cause the highest carbon stock and size diversity but the lowest NPV and species diversity, medium intensity would lead to a lower carbon stock but higher levels of species and size diversity and NPV, and high intensity would result in the lowest carbon stock and size diversity but the highest NPV and species diversity. An uncertainty analysis shows that the NPV, size diversity, and total carbon stock would be distinctively different in the business-as-usual climate scenario and the one representing all-out efforts to lower global emissions. However, for species diversity, climatic effects were mixed across different harvesting regimes.